Bioinspired Robust All‐Aqueous Droplet via Diffusion‐Controlled Interfacial Coacervation. (9th September 2020) - Huang, Xin; Tian, Li; Wang, Zhaoyue; Zhang, Jianqiang; Chan, Yu Suen; Cheng, Shuk Han; Yao, Xi
Abstract: All‐aqueous droplets demand structural and functional robustness to provide tailored microenvironments for various biomedical applications. Inspired by the structural supporting properties of eggshell membranes, all‐aqueous droplets with robust shells featuring optical transparence, compound permeability, and swelling resistance are developed. The dense coacervate shell encapsulates sodium alginate (Alg) droplets in a continuous ε‐poly‐l ‐lysine (ε‐PL) solution, via diffusion‐controlled interfacial coacervation between Alg and ε‐PL. Benefiting from the permeability of the coacervate shell, the core of the droplet presents embryo‐like stiffness‐responsiveness between the fluid and gel states via the perception of external microenvironment. Particularly, in a benchmarking comparison with Alg‐Ca 2+ hydrogel, the coacervate encapsulation presents boosted durability, mechanical robustness, and selective permeability in diverse conditions. This design strategy not only deepens the understanding on the design of all‐aqueous droplets with adaptive functions via one‐step interfacial coacervation between two miscible aqueous phases, but also broadens their feasibility as integrated platforms for biomedical applications. Abstract : Inspired by the functional and structural properties of eggshell membranes (ESMs), all‐aqueous droplets with robust shells are developed via diffusion‐controlled interfacial coacervation. The shells mimic bacterial resistance, selective permeability, mechanical stability, and swelling resistance of the ESMs. These features broaden the feasibility of all‐aqueous droplets as integrated platforms for biomedical applications.